Heterogeneous rock mass detection in the Goaf underlying the Yingbin substation - Dong, Jianjun; Zhang, Ying; Xie, Zhengquan; Gao, Ke (Frontiers in Earth Science, 2022)
The existence of heterogeneous rock mass in the goaf easily causes surface deformation, subsidence, and even collapse, which restricts the development of urbanization of the buildings above the goaf. Because of the saturation of the city and the shortage of power supply, the idea of building the Yingbin substation was proposed on the old coal mine goaf in Xinhua District, Pingdingshan City, Henan Province, China. To ensure the safety and stability of the foundation of the proposed substation, the comprehensive detection method was proposed, which is mainly based on transient electromagnetic detection and supplemented via drilling detection. It was used to determine the spatial position and location of heterogeneous rock mass in the goaf underlying the proposed substation. The results show that 1) after eliminating the interference to the transient electromagnetic detection, it is found that there are low-resistance anomalies near the depth of −160 m at points 1 to 2 and point 8 of the X2 line and at points 1 to 3 of the Y3 line, which are preliminarily presumed to be the influence of the heterogeneous rock mass. 2) The apparent resistivity anomalous areas of −160 and −200 m depth are highly consistent, and the location and scope of the heterogeneous rock mass were basically determined. 3) The abnormal depth range of core rate obtained by drilling is in good agreement with the abnormal range of apparent resistivity at the same location obtained by transient electromagnetic, which indicates the reliability of the detection results. 4) Combining the detection results of the two methods, the location and scope of the heterogeneous rock mass were basically determined, which is located in the western part of the proposed area. The detection results can provide a basis for the safety and stability of the proposed substation foundation. To ensure the safe and stable operation of the proposed substation foundation, effective governance measures for the heterogeneous rock mass of the goaf should be taken.